The South American paradigm of Congenital Heart Disease care - Lugones, Ignacio; Biancolini, María Fernanda (Journal of Humanitarian Cardiovascular Medicine, 2023)
South America is a land of contrasts. These contrasts encompass both nature and human activity. The health of individuals takes place within this context. In particular, congenital heart diseases, due to the complexity of their diagnosis and treatment, present a significant challenge for the region. Despite a large portion of the population lacking access to these services, the region is a pioneer in innovation in this field. Great surgeons from there have left an indelible legacy that still impacts the lives of people around the world today.